Effect of microalloying and thermomechanical treatment on the low-temperature fracture toughness of a high-strength weathering steel - Carlos E.G. Cortopassi; Marcio L.A. Cunha; Vitor S. Barbosa; Maicon M. Leivas; José H. Alano; Kleber E. Bianchi; Henara L. Costa (Journal of Materials Research and Technology)
Weathering steels have been used as structural materials for decades. Nevertheless, steel manufacturers have been forced to develop alternative alloys that offer better mechanical strength while maintaining the toughness and corrosion resistance of conventional weathering steels. This study employed microalloying with carefully selected elements to achieve grain refinement and appropriate corrosion resistance, combined with thermo-mechanical controlled processing (TMCP), to obtain a high-strength weathering steel. However, given the broad range of conditions in the global context, it is essential to assess the embrittlement mechanisms to which the material may be subjected, especially at low temperatures. This work aimed to evaluate the fracture behavior at low temperatures of two materials: i) a newly developed high-strength, microalloyed weathering steel produced in an initial industrial batch, and ii) ASTM A242 steel. The fracture toughness evaluation utilized the Temperature Transition Curve methodology. Nevertheless, the alternative steel performed worse than the ASTM A242 in the fracture tests. Visual examination on the fracture surfaces of the alternative steel specimens revealed significant delamination, referred to as splits. Metallographic and SEM/EDS analyses revealed numerous voids and vermicular-shaped fissures on the fracture surfaces, along with titanium carbonitride particles that were damaged during the fracture process. The results indicate that the benefits achieved through microalloying and TMCP can be hindered by the formation of large carbonitride particles during the casting stage. These particles, which remain largely unaffected in subsequent production steps, ultimately lead to a significant reduction in fracture toughness.